Fertility desire and associated factors among reproductive age women on anti-retroviral therapy in East Wollega public health facilities, west Ethiopia: facility based cross-sectional study - Fikadu, Worku (Frontiers in Reproductive Health, 2025)
BackgroundFertility desire in people living with HIV is the desire of people to have children in the future despite a diagnosis of HIV. The desire to have children among reproductive-age women living with HIV has signiﬁcant implications for the transmission of HIV to sexual partners and newborns in the future. There is no study conducted to determine the magnitude of the fertility desire among women of reproductive age living with HIV in East Wollega western Ethiopia. Therefore this study aimed to determine fertility desire and associated factors among women of reproductive age living with HIV receiving ART.ObjectivesTo assess fertility desire and associated factors among reproductive-aged women on antiretroviral treatment in East Wollega, West Ethiopia, 2023.MethodsA facility-based cross-sectional study was conducted in East Wollega from January 01/2023 to 30/2023. Data was collected from 419 study participants using interviewer-administered structured questionnaires by employing systematic random sampling techniques. Data entry and analysis were performed using Epi Data version 3.1 and SPSS version 23, respectively. Both bivariate and multivariate analyses were carried out using binary logistic regression. Statistical significance was established for variables with P < 0.05 in the multivariate analysis.ResultsAmong the 419 respondents, 166 (39.62%) reported that they desired to have children in the future. Age between 18 and 24 years (AOR = 2.49, 95% CI; 1.16, 5.35), having partner Living with HIV: (AOR = 0.50, 95% CI; 0.25, 0.9), and being married (AOR = 2.69, 95% CI; 1.65, 4.39) were significantly associated with fertility desire.ConclusionThe proportion of women of reproductive age living with HIV who desired children was high in this cohort. Understanding the fertility desire among women living with HIV/AIDS has a significant role in reducing perinatal transmission of HIV. Hence, Health care workers should provide intensive counselling regarding the possibility of the mother-to-child transmission of HIV.